2020
DOI: 10.3390/plants9121730
|View full text |Cite
|
Sign up to set email alerts
|

Psophocarpus tetragonolobus: An Underused Species with Multiple Potential Uses

Abstract: Natural products, particularly those extracted from plants, have been used as therapy for different diseases for thousands of years. The first written records on the plants used in natural medicine, referred to as “medicinal plants”, go back to about 2600 BC. A thorough and complete understanding of medicinal plants encompasses a multiplex of overlapping and integrated sciences such as botany, pharmacognosy, chemistry, enzymology and genetics. Psophocarpus tetragonolobus, a member of Fabaceae family also calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…For many years, P. tetragonolobus or winged bean has been widely utilized in traditional medicine as it contains several bioactive compounds. It is a member of Fabaceae family and is high in protein, oils, vitamins, and carbohydrates [45]. It has been reported that winged bean seed hydrolysate is non-toxic and can stimulate cell proliferation in NIH/3T3 mouse fibroblast cells [46] and winged bean extract was non-toxic to RAW264.7 macrophage cells [47].…”
Section: Resultsmentioning
confidence: 99%
“…For many years, P. tetragonolobus or winged bean has been widely utilized in traditional medicine as it contains several bioactive compounds. It is a member of Fabaceae family and is high in protein, oils, vitamins, and carbohydrates [45]. It has been reported that winged bean seed hydrolysate is non-toxic and can stimulate cell proliferation in NIH/3T3 mouse fibroblast cells [46] and winged bean extract was non-toxic to RAW264.7 macrophage cells [47].…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenol Anticarcinogenic, antioxidant, anti-inflammatory, antitumoral, antimicrobial, antimutagenic, anti-ischemic and anti-allergic properties (Mohanty et al, 2013;Bassal et al, 2020) Lectin Antiploliferative activity (Kortt, 1984) and prostate cancers due to their high intakes of legumes and legume products, which are good sources of saponins (Messina et al, 1994;Shi et al, 2004). Thus, they tend to have a longer life span than Africans (Lu et al, 2017).…”
Section: Winged Beanmentioning
confidence: 99%
“…Legume intake has also been found to be inversely associated with non-cardiovascular causes of death and overall total mortality. This is due to polyphenols that contains in legumes such as phenolic acid and flavonoids, which are known to alleviate CVD [8]. These benefits are optimal when three to four servings of legumes are consumed per day (equivalent to 375-500 g/day) [9].…”
Section: Introductionmentioning
confidence: 99%